How Job Creativity Requirements Affects Employee Creativity: Evidence From a Across-Level Analysis - Ma, Yingshuang; Zhang, Haomin; Dai, Yi (Frontiers in Psychology, 2021)
The present study adopted the Pygmalion perspective and a multilevel theoretical framework to investigate whether creative process engagement mediates the linkage of job creativity requirement with employee creativity. We examined whether team knowledge sharing moderates the aforementioned relationship. We obtained data from 71 supervisors and their 453 employees from three companies in China and applied Hierarchical Linear Modeling (HLM) version 6.08 to test the cross-level hypotheses. The results revealed that creative process engagement mediates the positive linkage of job creativity requirement with employee creativity. In addition, we observed that team knowledge sharing moderates the relationship among job creativity requirement, employee creativity, and creative process engagement. The practical and theoretical implications of the findings are discussed.